Genetic analysis of body conformation traits of indigenous Uttara chicken - MK Singh; S Kumar; RK Sharma; SK Singh; B Singh; DV Singh (Journal of Livestock Biodiversity, 2025)
This investigation aimed to evaluate genetics of body conformation characteristics in indigenous of Uttara chicken maintained at Govind Ballabh Pant University of Agriculture and Technology (India). Data was analysed using least squares analysis of variance technique. Least squares means of shank length, keel length and breast angle were estimated at 8 and 20 weeks of age. Sires of the chicks signi icantly (p<0.05) inluenced the estimates of all the traits throughout the ages. Male birds demonstrated better estimates than females at all stages. These results suggest that heritabilities are low for linear body measurements in the early period of growth in indigenous Uttara chickens. These research-outcomes may serve as base information to the breeders and academicians for chalking out breeding strategy in concerned aspect.